Vietnam : 2016 Article IV Consultation- Press Release; Staff Report; and Statement by the Executive Director for Vietnam. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that Vietnam's economy has experienced solid growth with low inflation, reflecting policy attention to maintaining macroeconomic stability. Economic performance was robust through most of 2015, driven by rapid export growth, foreign direct investment, and strong domestic demand. Manufacturing and exports moderated near year-end, reflecting slowing external demand. Inflation declined below 1 percent in 2015 before ticking upward in early 2016 owing to higher food and administered prices. For 2016, growth is projected to moderate to about 6 percent, reflecting the adverse agriculture shock, lower external demand, and spillovers of tighter global financial conditions.